Asesmen Formatif dalam Pembelajaran Matematika Memahami Perkembangan Siswa Secara Berkelanjutan - Kevin Ramadhani Pratama; Istiyati Mahmudah (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Formative assessment has become a key element in efforts to improve mathematics learning and understand student development on an ongoing basis. In the rapidly changing world of education, formative assessment provides educators with the tools necessary to effectively measure, monitor, and respond to individual student development. This article investigates the basic concepts of formative assessment and how this approach can be applied to mathematics teaching. We detail a variety of formative assessment methods that can assist educators in identifying students' strengths and weaknesses, and adapting instruction to fit their needs. The main point is to utilize formative assessment as a tool to open a window that reveals students' understanding of mathematical concepts, so that educators can provide more appropriate and effective support. This research also explains how formative assessment helps in facilitating the development of critical thinking and problem solving skills in students in the context of mathematics. The benefits of using formative assessments include improved student performance, a deeper understanding of individual needs, and the ability of educators to adapt the curriculum according to student development. Finally, this article summarizes how a formative assessment approach in mathematics learning can provide concrete benefits for educators, students, and the education system as a whole. With a focus on ongoing student understanding, formative assessments are an important tool in bridging learning gaps and helping students reach their full potential in mathematics.